Accurate coordination method based on the dynamic model of overcurrent relay for industrial power networks taking contribution of induction motors into account. Issue 4 (14th January 2020) - Ghotbi Maleki, Mahdi; Mohammadi Chabanloo, Reza; Farrokhifar, Meisam
Abstract : Induction motors are widely used in the industry. These motors contribute to short‐circuit currents (SCCs) by generating transient currents. The transient component in the SCC causes a change in the operating times of the overcurrent (OC) relays and miscoordination between the main and the backup relays. Therefore, the conventional relay coordination methods that use fixed SCCs for a specific fault location are not suitable for industrial power networks. In addition, the contribution of induction motors may cause a false trip in non‐directional OC relays at healthy feeder. Here, a method based on the dynamic model of the OC relay is proposed to take the effect of transient component of SCC into account in relays coordination. A new set of constraints is added to the conventional coordination constraints in order to solve the false trip issue. In this case, an optimisation algorithm is needed to coordinate non‐directional OC relays. The proposed method is implemented in a power network of cement factory and the results indicate the effectiveness of the proposed method. Here the genetic optimisation algorithm has been used and the simulation has been achieved using DIgSILENT and MATLAB software.